2020
DOI: 10.12962/j20882033.v31i1.5961
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Activities and Phenolic Content of Improved Soybean Seeds Varieties of Different Grain Sizes

Abstract: Tempe and tofu are the main product of soybean commonly consumed as a daily food for the people of Indonesia. So far, soybean is well known to be a source of protein. Indeed, soybean contains secondary metabolites resulting in antioxidant activities. Antioxidants would nullify the negative effect of reactive oxygen and, as a result, could improve and maintain human health. Improvement of awareness of Indonesian people that soybean is good for human health promotion and maintenance could be a trigger to enlarge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
1
Order By: Relevance
“…The results of the DPPH assay showed that the sprout of variety KH 10 showed higher DPPH activity (88.6% inhibition at 100 µg/mL) than the sprout of KH 8 (82.4% inhibition at 100 µg/mL). The DPPH activities of KH 8 and KH 10 sprouts were found substantially higher than the soybean sprout study of Soedarjo et al [33] (about 29% inhibition at 100 µg/mL). The results of the DPPH assay showed that the sprouts of variety KH 10 showed higher DPPH activity (88.6% inhibition at 100 µg/mL) than the sprouts of KH 8 (82.4% inhibition at 100 µg/mL).…”
Section: Ultrasonication Treatment On Antioxidative Potentialscontrasting
confidence: 67%
“…The results of the DPPH assay showed that the sprout of variety KH 10 showed higher DPPH activity (88.6% inhibition at 100 µg/mL) than the sprout of KH 8 (82.4% inhibition at 100 µg/mL). The DPPH activities of KH 8 and KH 10 sprouts were found substantially higher than the soybean sprout study of Soedarjo et al [33] (about 29% inhibition at 100 µg/mL). The results of the DPPH assay showed that the sprouts of variety KH 10 showed higher DPPH activity (88.6% inhibition at 100 µg/mL) than the sprouts of KH 8 (82.4% inhibition at 100 µg/mL).…”
Section: Ultrasonication Treatment On Antioxidative Potentialscontrasting
confidence: 67%
“…Total phenolic content (mg GAE/g sampel) of Indonesian improved soybean seeds possess high phenolic content. Phenolic content of Detam 1 (black soybean seed) was only half of the phenolic content of Indonesian yellow soybean seed, Detap 1 and Demas(Soedarjo et al 2019). Therefore, the genetics encoding for phenotypes other than the color of the soybean seed coat might also contribute to the phenolic profile.…”
mentioning
confidence: 97%